Qualitative Evaluation and Wound Healing Potential of Selected Medicinal Plants by Excision Wound Model: Qualitative Evaluation and Wound Healing Potential of Selected Medicinal Plants by Excision Wound Model - Kumar, Neelesh (International Journal of Pharmaceutical & Biological Archive, 2020)
Objective: The aim of the paper was to assess the wound healing potential of three medicinal plants using the excision wound healing model on albino rat. Materials and Methods: Soxhlet extraction method was utilized for the partition of the constituent of interest. Qualitative analysis and phytochemical screening were performed for the detection of tannins, alkaloids, resins, flavonoids, glycosides, steroids, proteins, carbohydrates, and amino acids. Three plants extract used for the ointment formulation and prepared by the addition of extract of Artocarpus heterophyllus, Murraya koenigii, and Punica granatum in polyethylene glycol ointment base. Three ointment formulations and six extracts with 5% and 10% extract concentration have been used. Excision wound rat model utilized for the wound healing potential. Results and Conclusion: All three plants, including A. heterophyllus Lam., M. koenigii Linn., and P. granatum Linn. extracted for the active constituent. The pharmacological evaluation on the excision wound healing model suggested that Group-I animals showed 52.09% of healing, whereas povidone-iodine treated animals showed 100.00% healing. On the other hand, the ointment formulation treated F-1 showed 96.47% of wound healing, F-2 showed 97.68% healing, and F-3 showed 99.11% healing. The overall healing results can be represented as following: Control <MKL5 <MKL10 <PGB5 <PGB10 <AHP5 <AHP10 <F-1 <F-2 <F-3 <Standard. F3 ointment formulation is better than the F2 and F1 formulation in wound healing potential as compared to others. Discussion: These studies have indicated that ointment formulations of A. heterophyllus, M. koenigii, P. granatum have been utilized for wound healing potential and it is safer for topical application. Excision wound healing model suggested that the three individual plant extract has shown the wound healing potential, although the prepared ointment formulations F3 have best and synergistic action than the individual. The ointment formulations containing plant extracts in 10% amount have better wound healing potential.